Behavior and gut microbiome of the stingless bee Partamona helleri under sublethal exposure to a leaf fertilizer and a bioinsecticide - Botina Jojoa, Lorena Lisbetd (2018)
The gut microbiome is related with nutritional health and immunocompetence of insects, besides is essential to neutralize impairs caused by pathogens or xenobiotics. Agrochemicals are regarded as one of the culprits often associated with the decline of bees, which occur by lethal and sublethal exposures during the foraging and, posteriorly with the food contamination within colony. In natural condition, is know that stingless bees have been submitted to chronic exposures by agrochemicals, which can compromise the gut microbiome and behavior in bees favoring for colony collapse, however, the effect of the leaf fertilizers and bioinsecticides remain neglected and are potentially important. Herein, we assess the sublethal effect of leaf fertilizer copper sulphate and bioinsecticide spinosad on forage bee behavior and gut microbiome composition of the stingless bee Partamona helleri (Friese), an important pollinator native in Neotropical region. Behavior bioassays and composition of gut microbiome were performed with forage bees orally exposed to LC 5 estimated from copper sulphate and spinosad. The characterizing of gut microbiota was through sequencing on illumina Miseq platform of the V4-V5 region of the bacterial 16S rRNA gene. The sublethal exposure to copper sulphate and spinosad did not affect in pattern on the overall activity, flight take-off and feed consumption. In contrast, copper sulphate decreases respiration rate and caused accumulation of copper in bodies of bees exposed. Neither copper sulphate nor spinosad altered the richness of the gut microbiome, but spinosad increased the differential abundance of the genus Gilliamella. In conclusion, agrochemicals considered safe for pollinators can exhibit high toxicity to stingless bees, revealing sublethal effects on physiology and changes in the differential abundance the gut microbiome of P. helleri. compromising the pollination services in Neotropical region that provide these pollinators, and therefore deserve further investigations.